Association of Myopic Deformation of Optic Disc with Visual Field Progression in Paired Eyes with Open-Angle Glaucoma. - Yu Sawada; Masanori Hangai; Makoto Ishikawa; Takeshi Yoshitomi (PLoS ONE, 2017)
The influence of myopia on glaucoma progression remains unknown, possibly because of the multifactorial nature of glaucoma and difficulty in assessing a solo contribution of myopia. The purpose of this study is to investigate the association of myopia with visual field (VF) progression in glaucoma using a paired-eye design to minimize the influence of confounding systemic factors that are diverse among individuals.This retrospective study evaluated 144 eyes of 72 subjects with open-angle glaucoma, with similar intra-ocular pressure between paired eyes, spherical equivalent (SE) ≤ -2 diopter (D), and axial length ≥ 24 mm. Paired eyes with faster and slower VF progression were grouped separately, according to the global VF progression rate assessed by automated pointwise linear regression analysis. The SE, axial length, tilt ratio and torsion angle of optic discs, Bruch's membrane (BM) opening area, and gamma zone parapapillary atrophy (PPA) width were compared between the two groups. Factors associated with faster VF progression were determined by logistic regression analysis.The mean follow-up duration was 8.9 ± 4.4 years. The mean value of SE and axial length were -6.31 ± 1.88 D and 26.05 ± 1.12 mm, respectively. The mean global visual field progression rate was -0.32 ± 0.38 dB/y. Tilt ratio, BM opening area, and gamma zone PPA width were significantly greater in the eyes with faster VF progression than those with slower progression. In multivariate analysis, these factors were significantly associated with faster VF progression (all P < 0.05), while SE and axial length were not associated with it.In myopic glaucoma subjects, tilt of the optic disc and temporal shifting and enlargement of the BM opening were associated with faster rate of VF progression between paired eyes. This suggests that myopia influences VF progression in glaucomatous eyes via optic disc deformations rather than via refractive error itself.